2013
DOI: 10.3892/or.2013.2298
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of DNA methylation enhances the therapeutic effect of gefitinib in non-small cell lung cancer cells

Abstract: The sensitivity of lung cancer to epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) has been found to be associated with mutations in the tyrosine kinase domain of EGFR. However, not all mutations are sensitive to gefitinib. While CpG island methylation in the promoter region of the EGFR gene and transcriptional silencing are common in solid tumors, the role of the EGFR gene promoter methylation in affecting resistance to TKIs in non-small cell lung cancer (NSCLC) remains unknown. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 35 publications
2
26
0
1
Order By: Relevance
“…31 We provide further evidence that TET1 is downregulated through MAPK signaling and that this occurs through the novel mechanism of ETS1-mediated upregulation of miR-29b, which targets TET1 for downregulation through an interaction with its 3′UTR (Figures 4 and 5), leading to downstream effects on 5-hmC levels (Figures 6 and 7). Several studies have shown synergy between histone deacetylase inhibition and MAPK inhibition 40, 41 as well as synergy between DNA-hypomethylating agents like 5-azacytidine and MAPK inhibitors, 42, 43 suggesting that DNA demethylation enhances the efficacy of MAPK inhibitors. More recently TET upregulation has been shown to be essential for active demethylation induced by 5-azacytidine.…”
Section: Discussionmentioning
confidence: 99%
“…31 We provide further evidence that TET1 is downregulated through MAPK signaling and that this occurs through the novel mechanism of ETS1-mediated upregulation of miR-29b, which targets TET1 for downregulation through an interaction with its 3′UTR (Figures 4 and 5), leading to downstream effects on 5-hmC levels (Figures 6 and 7). Several studies have shown synergy between histone deacetylase inhibition and MAPK inhibition 40, 41 as well as synergy between DNA-hypomethylating agents like 5-azacytidine and MAPK inhibitors, 42, 43 suggesting that DNA demethylation enhances the efficacy of MAPK inhibitors. More recently TET upregulation has been shown to be essential for active demethylation induced by 5-azacytidine.…”
Section: Discussionmentioning
confidence: 99%
“…It is of clinical interest that http://dx.doi.org/10.1016/j.jbiotec.2015.07.003 0168-1656/© 2015 Elsevier B.V. All rights reserved. NSCLC cells with EGFR promoter hypermethylation are resistant to EGFR inhibitor (Anglim et al, 2008;Jakopovic et al, 2013;Li et al, 2013;Montero et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Among the studies conducted on the treatment of NSCLC, studies involving the epidermal growth factor receptor (EGFR) target are widely respected. Although abnormal EGFR expression is ubiquitous in NSCLC patients (Easwaran and Baylin, 2012), there has been little investigation of the cause of the abnormal expression and its significance in clinical diagnosis and treatment (Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%